Establishment of suitable date of sowing and nutrient management for niger [Guizotia abyssinica (L.f.) Cass.]: Establishment of suitable date of sowing and nutrient management for niger [Guizotia abyssinica (L.f.) Cass.] - RAVI MORE; NISHA SAPRE; RAJANI BISEN; SURBHI JAIN (Journal of Oilseeds Research, 2020)
The experiment was conducted during the kharif 2018 at JNKVV, Jabalpur, Madhya Pradesh to find out the suitable date of sowing and nutrient management practice for niger. Sowing of niger in last week of September with application of 100% P & K and 50% N as basal and 50% N in equal splits (at 20 and 40 DAS) was the most suitable time of sowing and fertilizer management practice to get better seed yield and returns.